Disintegration from Within and Open Indonesian Identity - Sugeng Bayu Wahyono (Antropologi Indonesia, 2020)
This article analyzes various primordialistic conflicts coupled with ethnic and religious sentiments that occurred in the post-New Order Indonesia. It uses secondary data collected from various sources of literature. The analysis uses a cultural study approach that specifically focuses on the theory of essentialism and anti-essentialism concerning ethnicity and identity. Essentialism understands ethnicity and identity as a construct anchoring on a fixed and timeless value, while anti-essentialism understands it as a discursive in nature. By discussing the essentialist vis-à-vis anti-essentialist view in constructing state–religion relations in present day Indonesia, this article tries to reveal the underlying construct of Indonesian identity behind the tensions and conflicts between different ethnic and religious groups. It aims to offer an open construction of Indonesian identity as a strategy to neutralize the tendency of national disintegration from within.